The American Malacological Union Thirty-Fifth Annual Meeting Marinette, Wisconsin, July 21–25, 1969 (Hello World!, 1969)
This year's meetings were co-hosted by our Secretary , Margaret C. Teskey, and the University of Wisconsin-Green Bay, Marinette Center. Advance registration had already passed the hundred mark by the first day of the meetings and many more registered later.